Pengaruh Penempatan, Pelatihan, dan Motivasi Kerja Terhadap Semangat Kerja Karyawan PT. ASDP Indonesia Ferry (Persero) Cabang Balikpapan - Bagus Ferry Nugraha; Didik Hadiyatno; Imam Arrywibowo (MEDIA RISET EKONOMI [MR.EKO], 2022)
The purpose of this study was to determine the effect of Placement, Job Training and Motivationon the Moraleof the Employees of PT. ASDP Indonesia Ferry (Persero) in Balikpapan.The population in this study were permanent employees as much as 222 respondents.By using random sampling techniques so  the sample that  is in  use as much as 111respondents.Data collection techniques are observation, interviews and questionnaires.The data analysis technique used is Multiple Linear Regression using program SPSS v22. The  results  showed  Placement,  Job  Training  and  Motivationsimultaneously affect the Morale of employees PT. ASDP Indonesia Ferry (Persero)in Balikpapan. Motivationpartially hadsignificant influence and dominant to the morale of employees of PT. ASDP Indoensia Ferry (Persero) in Balikpapan.